(untitled) (CIPEEX, 2025)
Mental health refers to the state of psychological, emotional, and social well-being. It involves how people think, feel, and behave in their daily lives, influenced by biological, psychological, and environmental factors. The mental health of healthcare professionals has been widely discussed, particularly in high-demand settings such as Emergency Care Units (UPAs). These environments often present significant challenges, including occupational stress, intense workloads, and exposure to vicarious trauma, leading to disorders such as burnout, anxiety, and depression. This study evaluated the occurrence of Common Mental Disorders among healthcare professionals at the UPA in Ceres, Goiás. Ten professionals participated in the research, including three females and seven males, who answered the Self-Reporting Questionnaire - 20 (SRQ-20), comprising 20 mental health-related questions. Responses indicating seven or more "yes" answers signified mental distress. The results showed that all participants scored seven or higher, confirming significant mental distress. Occupational stress, intense workloads, lack of emotional support, and insufficient resources were identified as key contributors. The findings underscore the urgent need for interventions to support the mental well-being of healthcare professionals, ensuring both their welfare and the quality of care provided to patients. The study highlights the importance of implementing occupational health policies, psychological support measures, and self-care strategies to promote well-being and mitigate mental distress. Enhancing support for healthcare professionals is essential to improving their overall quality of life and maintaining high standards of patient care.